1974
DOI: 10.2307/2173959
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Birth Interval Dynamics in Rural Bangladesh

Abstract: A group of 209 married, fecund women in rural Bangladesh were studied prospectively for 24 months from 1969 to 1971 to define some of the biological and sociological factors relating to fertility performance. These women were selected from a larger study population of 112,000 that had been followed with a daily house-to-house vital registration programme since 1966. The selected women were interviewed bi-weekly and were asked questions about menstruation, pregnancy, lactation, husband's occupational absences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 0 publications
2
65
0
Order By: Relevance
“…A previous paper by Martin, Morley & Woodland (1964) described the birth interval of the area, and discovered an unexpectedly high overall mean interval of 35-5 months following the birth of a child who survived to 1 year. Since then, other studies from developing populations have produced estimates of birth intervals approaching 3 years (Potter et al, 1965;Cantrelle & Leridon, 1971;Chen et al, 1974). In this paper evidence will be presented from more extensive and recent data from Imesi to confirm the results first presented by Martin et al (1964), and to investigate the relationship between the birth interval and other variables, especially the survival and growth of the child.…”
Section: Introductionmentioning
confidence: 70%
“…A previous paper by Martin, Morley & Woodland (1964) described the birth interval of the area, and discovered an unexpectedly high overall mean interval of 35-5 months following the birth of a child who survived to 1 year. Since then, other studies from developing populations have produced estimates of birth intervals approaching 3 years (Potter et al, 1965;Cantrelle & Leridon, 1971;Chen et al, 1974). In this paper evidence will be presented from more extensive and recent data from Imesi to confirm the results first presented by Martin et al (1964), and to investigate the relationship between the birth interval and other variables, especially the survival and growth of the child.…”
Section: Introductionmentioning
confidence: 70%
“…At an aggregate level, van de Walle (1975) links the relatively low levels of marital fertility in nineteenth century Ticino, Switzerland to the regular seasonal pattern of male absence. Massey and Mullan (1984) use cross-sectional individual-level data from a rural town in Mexico to show that women with husbands absent through migration (leaving at some point between 1976 and 1978) were significantly less likely to have a child aged one or two (born in 1976 and 1977), while Chen et al (1974) argue that monthly variation in the number of days males are absent partially explains the striking seasonal pattern in births found in Matlab, Bangladesh over the two-year observation period.…”
Section: Disruptionmentioning
confidence: 99%
“…Sociobiol. 6 (1). Also, seasonal variations in plasma prolactin and milk yield were associated with significant differences in maternal nutrition and physical labor and were not explained by the frequency of infant feeding (1,3,4).…”
mentioning
confidence: 97%
“…In a prospective study in Bangladesh, Chen et al (6) found that the median duration of lactational amenorrhea with a surviving child was 17 months. This long period was related both to child feeding practices and to the poor nutritional status of the mother and child.…”
mentioning
confidence: 99%
See 1 more Smart Citation